Tarkowski w Łodzi - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Tarkowski in Łódź Exhaustively researched, Marek Hendrykowski’s study devoted to young Polish director Michał Tarkowski includes in-depth analysis and new readings of his student films (documentaries and features) made in the late 1970s in Lodz Film School. The author argues that in several respects Tarkowski’s etudes were perfect examples illustrating an original use of art-cinema conventions and forms by a skilful practitioner of what might be called the aesthetics of the bitter parody and contemporary grotesque.